Awareness and Perception of Investors towards the Mutual Fund Investment - Kandel, Madan; Sharma, Puja; Rajesh Kumar Poudel (Management Dynamics, 2024)
The study examines the awareness levels and perceptions of Nepalese investors toward mutual funds, with a focus on critical determinants such as financial literacy, risk perception, return expectations, and investment criteria. A structured survey was conducted among 115 investors in the Kathmandu Valley to assess their understanding, preferences, and challenges related to mutual fund participation. The findings show that although investors acknowledge the benefits of mutual funds, such as professional management and diversification, a significant knowledge gap still exists, with many lacking the financial literacy necessary to confidently navigate these instruments. Decision-making is heavily influenced by risk perception and return expectations, which frequently discourage potential investors because of perceived volatility or unfulfilled profit targets. Participation rates are also influenced by investing criteria, such as prior experiences and market openness. In order to allay investor concerns and promote trust, the report emphasizes the necessity of focused financial literacy initiatives, strengthened regulatory frameworks, and increased transparency. Policymakers, financial institutions, and fund managers are given helpful advice on how to match policies with investor demands and promote mutual fund expansion. Future studies should look at how digital platforms can make mutual fund education and accessibility easier on a national level.